Peroxisome Proliferator Activated Receptor gamma (PPARγ) Agonist Rosiglitazone Ameliorate Airway Inflammation by Inhibiting Toll-Like Receptor 2 (TLR2)/Nod-Like Receptor with Pyrin Domain Containing 3 (NLRP3) Inflammatory Corpuscle Activation in Asthmatic Mice - Cheng, Yinzhi (Med Sci Monit, 2018)
BACKGROUND: The purpose of this study was to explore the function and mechanism of peroxisome proliferator activated receptor agonist (PPARγ) in the toll-like receptor 2 (TLR2)/nod-like receptor with pyrin domain containing 3 (NLRP3) inflammatory corpuscle pathway of asthmatic mice. MATERIAL/METHODS: Eighteen female mice (C57) were randomly divided into 4 groups: the control group, the asthma model group challenged by ovalbumin (OVA), the rosiglitazone group, and the PPARγ agonist rosiglitazone treatment group. The infiltration of peribronchial inflammatory cells as well as the proliferation and mucus secretion of bronchial epithelial goblet cells were observed by hematoxylin and eosin and periodic acid-Schiff staining. Western blots were employed to detect the expression levels of TLR2, PPARγ, nuclear factor-kappa B (NF-kappaB), NLRP(3), and ASC [apoptosis-associated speck-like protein containing C-terminal caspase recruitment domain [CARD]). RESULTS: The number of inflammatory cells and eosinophils, and the levels of OVAs IgE, interleukin-4 (IL-4), and IL-13 were significantly higher in the C57 asthma group compared to the C57 control group and the treatment group (P<0.05). The infiltration of peribronchiolar inflammatory cells, wall thickening, goblet cell hyperplasia, and mucus secretion in the treatment group were all significantly decreased compared to those in the asthma group. PPARγ expression in the treatment group was significantly higher compared to the asthma group and the control group (P<0.05). The protein expression levels of TLR2, NF-kappaB, NLRP(3), and ASC were significantly lower compared to the asthma group but were higher compared to the control group (P<0.05). CONCLUSIONS: PPARγ rosiglitazone ameliorates airway inflammation by inhibiting NF-kappaB expression in asthmatic mice, and further inhibits the activation of TLR2/NLRP(3) inflammatory corpuscles.